An Easily Fabricated High Performance Fabry-Perot Optical Fiber Humidity Sensor Filled with Graphene Quantum Dots - Ning Wang; Wenhao Tian; Haosheng Zhang; Xiaodan Yu; Xiaolei Yin; Yonggang Du; Dailin Li (Sensors, 2021)
An easily fabricated Fabry-Perot optical fiber humidity sensor with high performance was presented by filling Graphene Quantum Dots (GQDs) into the Fabry-Perot resonator, which consists of two common single mode optical fibers. The relative humidity sensing performance was experimentally investigated by an interference spectrum drift between 11 %RH to 85 %RH. 0.567 nm/%RH sensitivity and 0.99917 linear correlation were found in experiments that showed high sensitivity, good and wide-range linear responding. Meanwhile, its good responding repeatability was demonstrated by two circle tests with increasing and decreasing relative humidity. For investigating the measurement influence caused by a temperature jitter, the temperature responding was experimentally investigated, which showed its linear responding with 0.033 nm/°C sensitivity. The results demonstrate the humidity sensitivity is greatly higher than the temperature sensitivity. The wavelength shift influence is 0.0198 nm with 0.6 °C max temperature jitter in the experiment, which can be ignored in humidity experiments. The fast-dynamic responses at typical humidity were demonstrated in experiments, with 5.5 s responding time and 8.5 s recovering time. The sensors with different cavity lengths were also investigated for their humidity response. All sensors gave good linear responding and high sensitivity. In addition, the relation curve between cavity length and response sensitivity also had good linearity. The combination of GQDs and single mode optical fibers showed easy fabrication and good performance for an optical fiber relative humidity sensor.